Survival after motor vehicle crash: impact of clinical and prehospital variables - Malvestio, Marisa Aparecida Amaro; Sousa, Regina Marcia Cardoso de (Revista de Saúde Pública, 2008)
OBJECTIVE: To assess clinical and prehospital variables associated with survival of motor vehicle crash victims. METHODS: Study carried out in the city of São Paulo (Southeastern Brazil), from 1999 to 2003. Data from 175 patients, who were aged between 12 and 65 years and had been motor vehicle crash victims, were analyzed. Kaplan-Meier Survival Analysis was used to approach the results at the accident scene with victims scoring